Estimation of drought tolerance of spring barley samples in their initial period of development on an osmotic solution - V. L. Gaze; I. A. Lobunskaya; P. I. Kostylev; E. G. Filippov (Зерновое хозяйство России, 2022)
Development of drought-tolerant spring barley varieties is one of the important breeding directions for resistance to abiotic stress factors. In order to solve this problem successfully, it is necessary to use in hybridization the varieties and lines with the highest tolerance. The main purpose of the current study was to estimate the effect of osmotic stress of different concentrations on seed germination and to evaluate the relative drought tolerance of spring barley varieties and lines. The study was carried out in the laboratory for plant physiology in 2018–2020. The estimation of drought tolerance of spring barley samples was carried out on 26 varieties and lines, bred in the ARC “Donskoy”, in the initial period of development. The laboratory experiments on the ability of spring barley seeds to germinate on a sucrose solution (imitation of a lack of moisture in the soil) make it possible to estimate drought tolerance of samples at the early stages of their development. There was studied an effect of a sucrose solution with an osmotic pressure of 3, 8, 10, 12, 14 atmospheres on the ability of seed germination. When increasing a concentration of the solution, there was a seed germination decrease in all genotypes. As a result of the study, there were the largest statistically significant differences (P > 0.95) of the samples under the concentration of the osmotic sucrose solution of 8 atmospheres, in comparison with the options of 3, 10, 12 and 14 atmospheres. There have been obtained the data on the relative drought tolerance of spring barley varieties and lines. The maximum indicators of seed germination under osmotic pressure of 8 atmospheres were registered among the samples ‘Zernogradsky 1716’ (91.1 %), ‘Zernogradsky 1717’ (85.9 %), ‘Zernogradsky 1719’ (84, 1%), ‘12545/18’ (80.2 %), ‘Zernogradsky 1701’ (78.9 %), ‘12551/18’ (72.9%), ‘12487/18’ (72.4%), ‘Zernogradsky 1724’ (70.6 %), ‘Zernogradsky 1721’ (69.8 %), ‘12525/18’ (69.2 %) in comparison with the standard variety ‘Ratnik’ (43.6 %). The identified samples can be used for further study of drought tolerance in the field.